Does the Time of Drug Administration Alter the Metabolic Risk of Aripiprazole? - Chipchura, Danielle A.; Freyberg, Zachary; Edwards, Corey; Leckband, Susan G.; McCarthy, Michael J. (Frontiers in Psychiatry, 2018)
Antipsychotic drugs cause metabolic abnormalities through a mechanism that involves antagonism of D2 dopamine receptors (D2R). Under healthy conditions, insulin release follows a circadian rhythm and is low at night, and in pancreatic beta-cells, D2Rs negatively regulate insulin release. Since they are sedating, many antipsychotics are dosed at night. However, the resulting reduction in overnight D2R activity may disrupt 24-h rhythms in insulin release, potentially exacerbating metabolic dysfunction. We examined retrospective clinical data from patients treated over approximately 1 year with the antipsychotic drug aripiprazole (ARPZ), a D2R partial agonist. To identify effects of timing on metabolic risk, we found cases treated with ARPZ either in the morning (n=90) or at bedtime (n=53), and compared hemoglobin A1c, and six secondary metabolic parameters across the two groups. After controlling for demographic and clinical factors, patients treated with ARPZ at night had a significant decrease in HDL cholesterol, while in patients who took ARPZ in the morning had no change. There was a non-significant trend towards higher serum triglycerides in the patients treated with ARPZ at night versus morning. There were no group differences in hemoglobin A1c, BMI, total cholesterol, LDL cholesterol or blood pressure. Patients taking APPZ at night developed a worse lipid profile, with lower HDL cholesterol and a trend towards higher triglycerides. These changes may pose additional metabolic risk factors compared to those who take ARPZ in the morning. Interventions based on drug timing may reduce some of the adverse metabolic consequences of antipsychotic drugs.